Kaffemik: Supporting a distributed JVM on a single address space architecture. - CAHILL, VINNY; WEBER, STEFAN (My University, 2001)
Java is increasingly used to develop large server applications. In order to provide powerful platforms for such applications a number of projects have proposed Java Virtual Machines (JVMs) that are based on network of workstations. These JVMs employ the message-passing paradigm, i.e. all communication between the distributed instances of the virtual machine take place using remote method invocation (RMI) or socket stream communication.
Java Virtual Machine Research and Technology Symposium
PUBLISHED
Keywords: Computer Science